Caracterização mineralógica e química das fontes de poeira e sua influência na atmosfera da região do polo cerâmico de Santa Gertrudes (SP) - Oliveira, Meyre [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Illiticas clays reserves outcropping in the vicinity of Rio Claro and Santa Gertrudes, were instrumental in the deployment of an Industrial Mining region specialized in the manufacture of flooring and glazed ceramic tiles, which currently accounts for over 50% of national production. While the sharp growth of these industries and the related mining activities, environmental problems also increased as the generation of wastewater, solid waste, and emissions of fluorides and particulates. In this context, this research studied the mineralogical and chemical compositions of the different geological materials, which are present in the ore extraction, transport, industries, and drying environments. Analytical results from the samples was collected in the four environments that are members of ceramic parts production chain characterized them as major emission particulates. Using a sequential sampler (Partisol), MP with diameter less than 10 micrometers were collected in the atmosphere of these areas, for chemical, mineralogical studies and subsequent correlation with the results obtained in the different domains of the productive segment characterization. Analytical techniques such as Xray diffraction, MEV ICP-ES, ICP-MS, and. chromatography for mineralogical and chemical characterization of geological materials, laser diffraction for particle size determination, confirmed that the levels of minerals and their chemical elements featured in both situations are genetically correlated. The inhalable set comprising major elements such as silica, aluminum, iron, titanium, potassium and trace elements such as barium, zirconium, fluoride and other characterized in the local atmosphere originates from the pellet of solid materials such as soils, ceramic materials used for roads to cover and ore during its extraction and exposure in drying area. The presence of fluoride detected in this atmosphere is attributed to emissions of the ceramic industry, ...

As reservas de argilas illiticas aflorantes no entorno das cidades de Rio Claro e Santa Gertrudes, foram determinantes para a implantação de um Polo Mineiro Industrial especializado na fabricação de pisos e revestimentos cerâmicos que, atualmente, responde por mais de 50% da produção nacional. Simultaneamente ao acentuado crescimento dessas indústrias e das atividades de mineração correlatas, cresceram também os problemas ambientais como geração de efluentes líquidos, resíduos sólidos, gasosos e material particulado. Nesse contexto, a presente pesquisa estudou as composições mineralógicas e químicas dos diferentes materiais geológicos, que estão presentes nos ambientes de extração do minério, transporte, secagem e das indústrias. Os resultados analíticos obtidos a partir de amostras coletadas nesses quatro ambientes os caracterizaram como principais fontes emissoras de materiais particulados. Utilizando um amostrador sequencial (Partisol), foram coletados materiais particulados com diâmetro inferior a 10 μm, para estudos químicos e mineralógicos da atmosfera local. Esses estudos foram correlacionados com aqueles obtidos nos diferentes domínios do segmento produtivo. As técnicas analíticas utilizadas como a difração de raios X, MEV ICP-ES e ICPMS e cromatografia para caracterização mineralógica e química dos materiais geológicos, e difração a laser para determinação granulométrica, confirmaram que os teores dos elementos químicos e respectivos minerais caracterizados em ambas as situações, são correlacionáveis geneticamente. O conjunto inalável composto de elementos maiores como sílica, alumínio, ferro, titânio, potássio e elementos traços como bário, zircônio, flúor e outros caracterizados na atmosfera local, têm origem na ressuspensão de materiais sólidos como os solos, materiais cerâmicos utilizados para capear estradas e no minério durante sua extração e exposição nos pátios...
Keywords: Air - Pollution; Ar - Poluição; Ar - Qualidade; Material cerâmico; Ceramica - Industria; Minerais de argila; Minas e recursos minerais; Meio ambiente; Santa Gertrudes (SP)